Konvergensi Pencegahan Stunting Di Desa Dringu Kabupaten Probolinggo - Taufikurrahman Taufikurrahman; Adi Prasetyo; Novia Ermilia Felda; Eka Nuraini; Dhea Setya Kusuma; Risa Pramestia Hani; Kaisa Tri Prawiswati; Muhammad Mufid Ro’uf; Ayii Maiha Febriani; Elvira Popy Eka Putri; Leiva Ayu Luxianto (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2024)
Stunting is a condition in which a child's development is disrupted by several factors, which one of the factor iis malnutrition. Stunting is a problem that often occurs in countries in the world, including Indonesia. In fact, the problem of stunting is one of the programs that is the main priority for the Government, namely efforts to accelerate the reduction of stunting rates program. Probolinggo Regency is one of the areas with a high stunting rate in East Java. Therefore, this service aims to be able to help provide education and understanding to the community so that they are more aware of the threat of stunting, especially the people of Dringu Village. To achieve this, various efforts need to be made, such as conducting outreach, education, Focus Group Discussion (FGD), to making appropriate products or technology that are in accordance with the conditions in Dringu Village. Where these activities have been carried out by targeting various groups, ranging from children, students to parents. Among children, education is carried out at PKK Sriwijaya Dringu Kindergarten. Meanwhile among students, socialization was carried out in several schools such as SDN Dringu. SDN Kedungdalem II, and SMAN Dringu. For parents, a Focus Group Discussion (FGD) activity was carried out where the Dringu Village community, Village Officials, Village Midwives, and Dringu District Nutritionists were invited. Our group also makes innovative products in the form of pudding from Moringa leaves. Moringa leaf pudding is one of the complementary foods for ASI (MP-ASI) which has many benefits. Not only that, the appropriate technology chosen by our group is in the form of maggot cultivation where the technology was chosen because it adapts to the conditions in Dringu Village. The various efforts that have been made by our group are basically carried out with the hope of helping to prevent stunting in Dringu Village.